Reading Comprehension Challenges and Their Contributing Factors Among EFL Students at SMPN 2 Kota Ternate - Novita Duyung; Indry Widyasti Anwar; Magvirah Octasary; Firmansyah Firmansyah (FKIP Universitas Khairun, 2026)
Reading comprehension remains one of the most challenging skills for English as a Foreign Language (EFL) learners, particularly at the junior high school level. This study aimed to identify the reading comprehension challenges faced by ninth-grade students at SMPN 2 Kota Ternate and to investigate the factors contributing to those challenges. The study employed a descriptive research design involving 34 students of class IX-1. Data were collected through a reading comprehension test consisting of five reading aspects, namely identifying main ideas, identifying references, making inferences, finding detailed information, and interpreting vocabulary. A questionnaire was also administered to identify linguistic and non-linguistic factors affecting students’ reading comprehension. The findings revealed that the students experienced substantial difficulties in reading comprehension, with an average score of 39.85, categorized as very poor. Among the five aspects assessed, vocabulary was identified as the most difficult aspect, followed by references and main ideas. The questionnaire results indicated that limited vocabulary mastery, insufficient grammar knowledge, lack of effective reading strategies, low motivation, limited background knowledge, and poor reading habits contributed to students’ difficulties. These findings suggest that reading instruction should focus not only on improving linguistic competence but also on developing reading strategies and motivation. More contextualized and interactive reading activities are recommended to support students’ reading comprehension development.